Population Dynamics of Microbial Communities in Mesotidal Estuarine Sediment of Iko River, Eastern Obolo, Akwa Ibom State, Nigeria - C. I. Udosen; S. I. Umana (Archives of Current Research International, 2018)
The population dynamics of microbial communities in mesotidal estuarine sediment of Iko River Estuary, Nigeria were investigated using standard microbiological and analytical procedures. The results revealed that the abundance of culturable microbes in the estuary varied between both tides as well as with the different microhabitats. Tidal influence had little or no impact on the heterotrophic and pollution indicator bacterial communities of the estuarine sediment but its influence on the activities of autotrophic bacterial communities was remarkable. The study revealed that 22.64% and 22.28% abundance rates of total heterotrophic bacteria were obtained during the high and low tides respectively. The abundance rates of 5.03% and 17.53% recorded for nitrogen-fixing bacteria and sulphate reducing bacteria respectively during high tide were higher than 4.07% and 10.93% obtained during low tide. Bioaerosols concentrations were found to be higher during high tide than low tide. Geographic Information System (GIS) models of microbial communities revealed marked variation which ranged between tidal influences and locations. The model revealed high concentrations of microorganisms in the north-west zone during both tides, while fungi were highly concentrated in the north-east zone during high tide. High species richness was observed, but with little or no tidal influences and isolates included known pathogenic species. The total organic carbon content of the sediments during both tides were higher than an optimum value of 1.3%, with a high linear correlation (r = 0.777) between heterotrophic bacteria load and organic content level of the sediment during low tide indicating a relatively high content of organic matter in the sediments can increase the bacterial load. The study therefore calls for effective environmental monitoring.